Adherence to the Healthy Eating Index-2015 (HEI-2015), Cognitive Function, and Incident Dementia in the Atherosclerosis Risk in Communities (ARIC) Study (OR32-01-19). (13th June 2019) - Hu, Emily; Wu, Aozhou; Dearborn, Jennifer; Gottesman, Rebecca; Steffen, Lyn; Coresh, Josef; Rebholz, Casey
Abstract: Objectives: The Healthy Eating Index-2015 (HEI-2015) score was created to measure adherence to the 2015–2020 Dietary Guidelines for Americans . It remains undetermined whether adherence to the newly released guidelines is associated with improved cognitive function or reduced incident dementia. Methods: We assessed the diet of 13, 632 participants from the Atherosclerosis Risk in Communities (ARIC) study who were recruited from 1987–1989 and calculated their HEI-2015 scores (0–100) using responses to food frequency questionnaires. Baseline cognitive function was assessed using the Delayed Word Recall, Digit Symbol Substitution, and Word Fluency Tests. We used linear regression models to assess the cross-sectional association of adherence to HEI-2015 and standardized cognitive test scores. Incident dementia was ascertained through the end of 2017. Dementia status at the ARIC Neurocognitive Study visits (2011–13, 2016–17) was determined by detailed neurocognitive battery, informant interviews, and adjudicated review as well as through dementia screening by phone interview and informant review, or by ICD-9 dementia code for a hospitalization or death. We used Cox proportional hazards regression models adjusted for demographic, lifestyle, genetic, and clinical covariates to estimate the association between HEI-2015 score and risk of incident dementia. Results: Compared to participants in the lowest quintile of HEI-2015 score, participants in the highest quintile scored higher on the Digit Symbol Substitution Test (β: 0.07, 95% CI: 0.03 to 0.11, P for trend < 0.001), Word Fluency Test (β: 0.07, 95% CI: 0.02 to 0.12, P for trend < 0.001) and global cognitive score (β: 0.05, 95% CI: 0.01 to 0.10, P for trend = 0.003) (Table). In total, there were 2354 cases of incident dementia over a median follow-up of 25 years. Compared to participants in the lowest quintile, participants in other quintiles had a lower risk of incident dementia after adjusting for covariates. Participants in the highest quintile had a 19% lower risk of dementia compared to those in the lowest (HR: 0.81, 95% CI: 0.71–0.93, P for trend = 0.01). Conclusions: Higher adherence to the 2015–2020 Dietary Guidelines for Americans was associated with higher baseline cognitive function and lower risk of incident dementia. Funding Sources: NHLBI, NIDDK, NIA, NINDS, NIH, HHS. Supporting Tables, Images and/or Graphs: